2016
DOI: 10.1111/bor.12176
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Borrobol Tephra

Abstract: The Borrobol Tephra has been identified as one of the key tephra horizons for the Lateglacial time period but it also exemplifies many of the promises and problems of tephrochronology. Additional horizons with similar major element composition and approximately the same age have been identified around the North Atlantic region. Here, we revisit the Borrobol Tephra identified at two Swedish sites, H?sseldala port and Skallahult, and also the Borrobol type-site in Scotland. We present the first set of minor elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 70 publications
(175 reference statements)
0
48
0
Order By: Relevance
“…Sweden: (25) Hässeldala port (Davies et al ., , ; Lind et al ., ). (26) Skallahult (Davies et al ., ; Lind et al ., ). Denmark: (27) Østerskov (Larsen, 2014 cited in Lind et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Sweden: (25) Hässeldala port (Davies et al ., , ; Lind et al ., ). (26) Skallahult (Davies et al ., ; Lind et al ., ). Denmark: (27) Østerskov (Larsen, 2014 cited in Lind et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…(26) Skallahult (Davies et al ., ; Lind et al ., ). Denmark: (27) Østerskov (Larsen, 2014 cited in Lind et al ., ). Germany: (28) Lake Hämelsee (Jones et al ., ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the North Iceland shelf, Gudmundsdóttir et al () identified a ‘Borrobol‐like' tephra in MD99‐2272 and attached an age to it of 14.5 cal ka BP; this identification was used in the Xiao et al () paper. The similarity coefficient (Sarna‐Wojcicki et al ., ) between the B997‐338 tephras and the geochemistry of the type Borrobol (Lind et al ., ) suggests the closest match with the geochemistry at 90 cm. If correct, this supports the larger Δ R age estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Their equivalent rhyolitic glass composition is referred to collectively as ‘Borrobol‐type’, after its first detection in early Interstadial sediments at the Borrobol type‐site in northern Scotland (Turney et al , ). They occur singly or together in a number of terrestrial sequences in northern Europe (summarised by Lind et al , , and references therein). The recent detection of Borrobol‐type cryptotephras in early Interstadial Greenland ice (Cook et al , ) marks a possible further correlation with one or more of these layers in this valuable high‐precision record.…”
Section: Introductionmentioning
confidence: 99%